Exploring Clinical Pathway for Incomplete Abortion and Strategic Improvement Efforts: An Action Research Study - Faisal, Yusuf Nur; Kusbaryanto, Kusbaryanto (Universitas Muhammadiyah Yogyakarta, 2025)
Clinical pathways (CP) are an evidence-based guideline designed for quality control and cost control of patient care. Clinical pathway compliance at one of the type C private hospitals in Indonesia (TCPH) was recorded at 0% during the first five months of 2023. This study aims to explore the factors influencing the application of the Clinical pathway for incomplete abortion and identify potential strategies to improve its utilization through an action research approach. This qualitative study employed two intervention cycles, including evaluation, identification of barriers, and socialization and education. Data were collected through Focus Group Discussions and were analyzed thematically. The study explored various aspects of CP implementation and evaluation for incomplete abortion, focusing on compliance assessment. The primary barriers identified were inadequate socialization, limited understanding, and restricted access to CP documents. Improvement strategies included providing medication packages, enhancing socialization efforts, and standardizing procedures across service units. Socialization was crucial in ensuring healthcare providers understood and adhered to CP, ultimately enhancing service effectiveness. The implementation of the incomplete abortion CP remains suboptimal due to the lack of audits, compliance monitoring, and socialization, leading to inconsistencies in care and reduced service effectiveness. A formal audit, strengthened monitoring, and improved socialization are necessary to ensure treatment uniformity and enhance service quality.